Spatial Variability in the Distribution of Fuel Stations Along Main Roads in Wasit Governorate Using Geographic Information Systems - Noshi Mohammed, Lect . Dr. Wassan (Basra studies journal, 2025)
This study examines the spatial distribution of fuel stations along the main streets of Wasit Governorate using Geographic Information Systems (GIS). GIS has emerged as a crucial tool for analyzing the spatial patterns of service center distribution. The research aims to evaluate the distribution patterns of fuel stations, assess their relationship with spatial characteristics and surrounding geographical variables, and determine their sufficiency and efficiency. By applying statistical methods, particularly buffer zone analysis, the study found that most fuel stations along the main streets in Wasit Governorate fail to meet the required distance standards. Exceptions include the Al-Amal Road stations located on Kut-Baghdad Street and the Abu Raghif stations situated on Kut-Maysan Street. This highlights the random and unorganized placement of fuel station sites, which do not adhere to the established standards set by the relevant authorities. The research provides practical recommendations based on the results and insights gained from GIS analysis, aiming to improve the planning and organization of fuel station distribution in the region.